Factors influencing the nutritional behavior of Syrian migrants in Germany - results of a qualitative study - Alexandra Sauter; Salma Kikhia; Julia von Sommoggy; Julika Loss (BMC, 2021)
Abstract Background Syrian migrants represent the third-largest group of foreigners in Germany and are therefore potential users of health promotion initiatives, including nutrition programs. It is little known how (healthy) nutrition is understood and implemented by this group and which factors influence their experiences related to food and eating in the host country. Thus, this study aimed to explore the importance of (healthy) nutrition, facilitators, and barriers of a preferred diet; nutritional changes in relation to the country of origin; and how nutrition may change with increasing length of stay. Methods Thirty semi-structured qualitative interviews with Syrian migrants (male = 16, female = 14, 18-35 years, length of stay 10-68 months) were conducted in 2018. Seventeen migrants could be followed-up after 12 months and were interviewed in 2019 again and were asked for changes in their nutritional behavior. Interviews were conducted in German, English, or Arabic, transcribed and translated into English if necessary. For analysis, an abbreviated version of the Grounded Theory was used. Results We identified six overarching themes that described influencing factors on a favored diet in Germany over the course of stay: (1) managing everyday life; (2) intercultural contact with local residents; (3) social context of cooking and eating; (4) ambiguity toward Arabic food; (5) mistrust toward certain types of food; and (6) influence of postmigration stressors. In general, the importance of nutrition is high among Syrian migrants. However, daily stressors, the lack of practical knowledge of how to cook favored dishes, and food insecurity in the new food environment make it difficult to obtain a preferred diet. With increasing stay, many developed a higher awareness of healthy eating, mainly due to a new independence or influences from the social environment in Germany. Conclusion Results highlight the need for health promotion interventions to be more responsive to the specific needs of Syrian migrants, including nutrition. Syrian migrants differ in their capabilities, needs, and aims, and they should be addressed differently by health professionals, social services or migrant specific services. Future research should continue to focus on the living conditions of Syrian migrants and its influence on nutrition.